Impact of duration of treatments with metformin and sulfonylureas, individually or in combination, on diabetic retinopathy among newly diagnosed type 2 diabetic patients: a pooled cohort’s analysis - Mansour Bahardoust; Yadollah Mehrabi; Farzad Hadaegh; Davood Khalili; Ali Delpisheh (International Journal of Retina and Vitreous)
Abstract Background This study aimed to evaluate the effect of metformin and sulfonylurea (SUs) medication time on Diabetic retinopathy (DR) among newly diagnosed patients with type 2 diabetes (T2DM) using a pooled analysis. This study aimed to evaluate the effect of metformin and SUs’ medication time on DR among newly diagnosed T2DM using a pooled analysis. Methods The data of 4,068 newly diagnosed DM individuals(mean age, 60.2 ± 0.85 years) from three prospective cohorts of Tehran Sugar and Lipid Study (TLGS), Multi-Ethnic Study of Atherosclerosis (MESA), and Atherosclerosis Risk in Communities (ARIC) with a mean age of 59.6 ± 08 years were pooled. The cumulative exposure to metformin, SUs, aspirin, statin, and anti-hypertensive medication was also determined using the same approach. The Cox proportional hazards (CPH) model was used to calculate the hazard ratio (HR) (95% CI) for the outcomes while adjusting for confounding factors such as fasting Blood Sugar (FBS), age, statin, aspirin, and anti-hypertensive medications. Results During follow-up, DR occurred in 519 DM. Metformin alone, SUs alone, and the combination of both reduced the hazard of DR by 10%, 7%, and 11% for each year of use, respectively (p < 0.05). The protective effect of metformin and SUs, individually or in combination, on DR started approximately five years after the initial treatment and continued until approximately 15 years after the initial treatment and then reached a plato. Conclusion Long-term treatment with metformin and SUs, individually and in combination, was associated with a reduced risk of DR in people with newly diagnosed diabetes for up to a decade compared with no treatment. These findings highlight the protective role of metformin and sulfonylureas as inexpensive and readily available drugs to prevent DR in people with newly diagnosed diabetes.